2022
DOI: 10.1007/s40487-022-00205-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Prognostic Significance of Stem Cell Marker CD133 in Survival Rate of Patients with Colon Cancer

Abstract: Introduction Today, colon cancer is one of the most common types of gastrointestinal cancer worldwide. CD133 as a known cancer stem cell marker has been found effective in cell proliferation and differentiation in various cancers, including colon cancer. We aimed to investigate the relationship between CD133 expression in colon cancer with prognostic factors and survival rate of patients with colon cancer by immunohistochemistry. Methods Formalin-fixed paraffin-embedded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…As we moved from the proximal to the distal colon, there was a significant (p=0.025) increase in CD133 expression (Table 2). The incidence of high CD133 expression was maximum in the rectum (83.3%) and lowest in the right colon (25.0% [23,24]. However, none of these studies have explained the difference in CD133 expression at different sites of the large intestine.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As we moved from the proximal to the distal colon, there was a significant (p=0.025) increase in CD133 expression (Table 2). The incidence of high CD133 expression was maximum in the rectum (83.3%) and lowest in the right colon (25.0% [23,24]. However, none of these studies have explained the difference in CD133 expression at different sites of the large intestine.…”
Section: Discussionmentioning
confidence: 95%
“…Pop et al and Park et al also found increased CD133 expression in the distal part, but the difference was not statistically significant [ 21 , 22 ]. In contrast, Kostovski et al and Ehteram et al found higher CD133 expression in tumors occurring in the proximal part of the colon, but the difference was not significant [ 23 , 24 ]. However, none of these studies have explained the difference in CD133 expression at different sites of the large intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristic features of tumor stem-like cells include spherical formation, self-renewal to secondary neurospheres or subspheres, and expression of stem-like markers of their corresponding parental tumors . In our study, we have considered the expression of CD133, CD44, Nestin, VIM, and SOX2 as indicative of stemness markers, IDH1 as a diagnostic marker of gliomas, GFAP as an astrocytic marker; and βIII-tubulin as a representative of neuronal differentiated cells . Our developed spheroids have shown enhanced self-renewal with expression of stemness gene markers of VIM, Nestin, CD44, GFAP, IDH1, and βIII-tubulin, which were confirmed by proteomic analysis.…”
Section: Discussionmentioning
confidence: 97%
“…CD133 (Prominin 1, PROM1) is a transmembrane protein whose mRNA and glycosylated forms are highly expressed in a variety of human cancer cells. CD133 is a cancer stem cell (CSC) marker and is associated with cancer progression and patient prognosis [ 114 , 115 ], including pancreatic cancer [ 116 ], colorectal cancer [ 117 ] and breast cancer [ 118 , 119 ]. Besides the application of CD133-targeted CAR T-cells in MLL leukemia [ 120 ], anti-CD133 CAR T-cells have been reported in a phase I trial including 14 patients with hepatocellular carcinoma (HCC), 7 patients with pancreatic carcinomas, and 2 patients with colorectal cancer [ 121 ].…”
Section: Car T-cell Therapy In Solid Tumorsmentioning
confidence: 99%